2004
DOI: 10.1897/03-166
|View full text |Cite
|
Sign up to set email alerts
|

Surveys of plasma vitellogenin and intersex in male flounder (Platichthys flesus) as measures of endocrine disruption by estrogenic contamination in United Kingdom estuaries: Temporal trends, 1996 to 2001

Abstract: Plasma vitellogenin (VTG) concentrations and the presence of the ovo-testis (intersex) condition have been recorded in male flounder (Platichthys flesus) captured from several United Kingdom (UK) estuaries since 1996 as part of the endocrine disruption in the Marine Environment (EDMAR) project and earlier programs. It has been confirmed that plasma VTG concentrations in male flounder have remained elevated in several UK estuaries (e.g., Tees, Mersey, and Tyne) throughout the period covered by this study. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 27 publications
8
79
1
3
Order By: Relevance
“…The range and magnitude were also similar to the lower end of those reported for wild flounder in the United Kingdom or the Netherlands [36,37] and in freshwater studies involving either wild roach [38] or caged rainbow trout [39] held for three to four weeks downstream of sewage effluent outfalls in the United Kingdom. Also, although some studies on rainbow trout have reported adverse reproductive effects associated with 10-to 30-fold VTG elevation [2,11], adverse reproductive effects also have been reported with only two to three fold VTG elevation, which are levels similar to those observed in the current study.…”
Section: Discussionsupporting
confidence: 78%
“…The range and magnitude were also similar to the lower end of those reported for wild flounder in the United Kingdom or the Netherlands [36,37] and in freshwater studies involving either wild roach [38] or caged rainbow trout [39] held for three to four weeks downstream of sewage effluent outfalls in the United Kingdom. Also, although some studies on rainbow trout have reported adverse reproductive effects associated with 10-to 30-fold VTG elevation [2,11], adverse reproductive effects also have been reported with only two to three fold VTG elevation, which are levels similar to those observed in the current study.…”
Section: Discussionsupporting
confidence: 78%
“…compounds that act as the female sex hormone 17b-estradiol. The most notable effect in this respect is the intersexuality of male fish that is observed at large scale in the UK (Jobling et al 1998;Allen et al 1999a,b;Kirby et al 2004) and other countries (Sole et al 2003;Barnhoorn et al 2004;Vethaak et al 2005;Bjerregaard et al 2006;Houtman et al 2007). Intersex male fish developed female characteristics, i.e.…”
Section: Endocrine Disrupting Compoundsmentioning
confidence: 99%
“…Male flounders (Platichthys flesus) caught in industrialised estuaries of the UK and the Netherlands have been found with elevated concentrations of VTG in their plasma (Lye, Frid, Gill, & McCormick, 1997;Lye, Frid, & Gill, 1998;Allen et al, 1999a;Allen et al, 1999b;Matthiessen, Allen, Bamber, Craft, Hurst, Hutchinson et al, 2002;Vethaak, Lahr, Kuiper, Grinwis, Rankouhi, Giesy et al, 2002;Kirby, Allen, Dyer, Feist, Katsiadaki, Matthiessen et al, 2004;Kleinkauf, Scott, Stewart, Simpson, & Leah, 2004b;Kirby, Smith, Barry, Katsiadaki, Lyons, & Scott, 2006). The range of VTG concentrations was great (from <0.01 µg/ml to >50 x 10 3 µg/ml).…”
Section: Comparison With Previous Studies On Estrogenic Eds On Marinementioning
confidence: 99%